A metal diatomic site cobalt-iron supported nitrogen-doped nanocarbon material, a preparation method thereof and application thereof in lithium-oxygen batteries
Patent Information
- Application Number
- CN202311489657.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-09
AI Technical Summary
正极催化剂加速了绝缘放电产物导致的缓慢反应动力学,目前气体正极面临的主要挑战如下:(1)放电产物Li2O2会堵塞多孔电极,降低锂氧气电池的容量,随着放电产物的形成和积累会引起正极严重钝化,导致电池失效
[0021](1)本发明通过真空辅助热处理法制备了一种纳米棒组装菱方八面体状氮掺杂纳米碳前驱体,并通过负载铁和钴元素,制备了金属活性位点高度分散的钴/铁双金属氮掺杂纳米碳材料,具有高度ORR/OER双功能催化活性,可作为有机体系锂氧气电池的正极催化材料。
Smart Images

Figure CN117317264B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a nitrogen-doped nanocarbon material supported by cobalt-iron at two atomic sites, its preparation method, and its application in lithium-oxygen batteries. In particular, it relates to an atomically bimetallic cobalt-iron supported nitrogen-doped nanocarbon material and its application in lithium-oxygen batteries, belonging to the field of nanocarbon materials / metal-air battery technology. Background Technology
[0002] As human society's demand for electricity, especially portable power sources, increases, so too does the requirement for battery energy density. Lithium-oxygen (Li-O2) batteries, composed of an oxygen cathode, a lithium metal anode, and an electrolyte, boast a theoretical energy density of up to 3500 Wh / kg, ranking among the top existing battery systems. This extremely high energy density primarily stems from two sources. Firstly, the cathode: lithium-oxygen batteries use a gaseous catalyst electrode instead of the traditional metal oxide cathode, significantly reducing battery weight. Secondly, the anode: lithium-oxygen batteries use lithium metal as the anode, and the extremely low electrode potential and high specific capacity of lithium metal greatly enhance the energy density of lithium-oxygen batteries. While lithium-oxygen batteries use oxygen as the cathode reactant and theoretically possess an infinitely large capacity, a catalyst with a certain level of catalytic activity is still required to complete the charge-discharge process. Therefore, the performance of the cathode catalyst is crucial for improving the specific capacity of lithium-oxygen batteries, reducing the overpotential of the charge-discharge reaction, and thus significantly increasing the battery's energy density.
[0003] The positive electrode performance of lithium-oxygen batteries is determined by the formation / decomposition process of discharge products, mainly affected by ORR / OER (oxygen reduction reaction / oxygen evolution reaction). A typical positive electrode usually consists of a catalyst, a conductive agent, and a binder connected to a porous conductive framework. The positive electrode catalyst accelerates the slow reaction kinetics caused by the insulating discharge products. The main challenges currently faced by gas positive electrodes are as follows: (1) The discharge product Li2O2 will block the porous electrode, reduce the capacity of the lithium-oxygen battery, and the formation and accumulation of discharge products will cause severe passivation of the positive electrode, leading to battery failure. (2) Intermediate products in the battery discharge process, such as superoxide (O2) - O2 2- Li2O2 (such as LiO2) will attack the cathode carbon material, producing unnecessary byproducts that are difficult to decompose, thereby greatly reducing the cycle efficiency. (3) The intrinsic insulation of Li2O2 determines the hysteresis kinetics of OER. The high charging voltage (>4.5V) caused by the large overpotential will inevitably cause the decomposition of electrode material and part of electrolyte, forming insoluble byproducts, which will then undergo parasitic reactions with Li2O2, resulting in low coulombic efficiency. At present, a large number of studies have explored various cathode catalysts to reduce the overpotential during the charging and discharging process of lithium oxygen batteries, and improve the discharge capacity, coulombic efficiency and cycle stability of the battery.
[0004] Developing efficient bifunctional catalysts that simultaneously exhibit ORR and OER catalytic activity to improve energy conversion efficiency and battery cycle stability from a kinetic perspective is one of the main challenges of rechargeable lithium-oxygen batteries. Currently, Pt-based and Ir-based catalysts are the most well-known ORR and OER catalysts, respectively, with excellent catalytic effects, but they also have the disadvantages of low abundance and high cost. Therefore, carbon-based catalysts with carbon materials as the matrix and transition metals supported to replace noble metal catalysts have received widespread attention. Among them, MOF-derived dual-atom-site catalysts (DASCs) with metal-nitrogen-carbon structures have been applied to the electrocatalytic oxidation of CO because they not only have the characteristics of maximizing atom utilization and isolating active sites (SmallMethods, 2019, 3(9): 1800480; Nanoscale, 2018, 10(33): 15696-15705.), but their application as cathode catalysts in lithium-oxygen batteries has not yet been reported. Moreover, the synergistic effect of bimetallic sites can simultaneously achieve highly efficient electrocatalysis of ORR and OER, making it the most promising oxygen electrocatalyst. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention aims to provide a nitrogen-doped nanocarbon material supported by cobalt and iron at two metallic atomic sites, its preparation method, and its application in lithium-oxygen batteries. The invention loads a predetermined ratio of cobalt and iron atoms onto a nitrogen-doped nanostructured carbon matrix and applies it to lithium-oxygen batteries. By replacing precious metals with transition metals, production costs are reduced, and the energy conversion density and cycle life of lithium-oxygen batteries are improved.
[0006] The objective of this invention is achieved through the following technical solutions.
[0007] A nitrogen-doped carbon nanomaterial supported on cobalt and iron with two atomic sites, the nitrogen-doped carbon nanomaterial comprising a nitrogen-doped carbon substrate with a porous structure and atomically distributed iron and cobalt sites supported on the nitrogen-doped carbon substrate.
[0008] A method for preparing nitrogen-doped carbon nanomaterials supported on cobalt-iron with two atomic sites, the method comprising the following steps:
[0009] The first step involves mixing an aqueous solution of zinc acetate dihydrate and an aqueous solution of benzimidazole to obtain a mixture. The mixture is then heated under vacuum in a vacuum oven to obtain a white powdered zeolite imidazole-based metal-organic framework (ZIF-7). The obtained white powdered zeolite imidazole-based metal-organic framework (ZIF-7) has a rhombohedral octahedral structure with self-assembled nanorods. This structure has a porous structure and a large specific surface area. The obtained white powdered zeolite imidazole-based metal-organic framework (ZIF-7) is then added to a tetrahydrofuran solvent to obtain a ZIF-7 solution.
[0010] The second step involves mixing cobalt and iron sources in tetrahydrofuran to obtain a blue-green suspension. The blue-green suspension is then poured into the ZIF-7 solution obtained in the first step and stirred for 22-26 hours. After stirring, the mixture is centrifuged, and the product is washed with ethanol and dried to obtain a zeolite imidazole-based metal-organic framework ZIF-7 composite material containing iron and cobalt ions.
[0011] The third step involves carbonizing the ZIF-7 composite material obtained in the second step at 950-1000℃ for 2-3 hours under a nitrogen or inert gas protective atmosphere to obtain nitrogen-doped nanocarbon materials supported by cobalt and iron. After etching with hydrochloric acid, nitrogen-doped nanocarbon materials supported by atomic-level bimetallic cobalt and iron are obtained, namely nitrogen-doped nanocarbon materials supported by cobalt and iron with metal dual atomic sites. The resulting product is a rhombohedral octahedral nitrogen-doped nanocarbon material assembled by nanorods supported by atomic-level bimetallic cobalt and iron derived from ZIF-7.
[0012] In the first step, the concentration of the aqueous solution of zinc acetate dihydrate is 20-24 mg / mL, the concentration of the aqueous solution of benzimidazole is 20-24 mg / mL, and the mass ratio of the solute in the aqueous solution of zinc acetate dihydrate to the solute in the aqueous solution of benzimidazole is 0.2-0.3:1; when mixing the aqueous solution of zinc acetate dihydrate and the aqueous solution of benzimidazole, it means pouring the aqueous solution of zinc acetate dihydrate into the aqueous solution of benzimidazole under stirring; the pressure of the vacuum oven is 0.02-0.10 MPa, the temperature of the vacuum oven is 78-82℃, and the constant temperature heating time is 24-36 h;
[0013] In the first step, the concentration of the ZIF-7 solution is 8-12 mg / mL;
[0014] In the second step, the molar ratio of cobalt source to iron source is 0.25-4:1, the drying temperature is 55-60℃, the concentration of tetrahydrofuran solution of iron source is 1-4 mg / mL, the cobalt source is cobalt phthalocyanine, the iron source is iron phthalocyanine, and the mass ratio of cobalt phthalocyanine to iron phthalocyanine and to zeolite imidazole metal-organic framework ZIF-7 is 0.02-0.04:1.
[0015] In the third step, the hydrochloric acid concentration is 0.5-1 mol / L, and the acid etching process is performed by ultrasonication at an ultrasonic power of 200-220W for 10-30 minutes.
[0016] Application of a nitrogen-doped nanocarbon material supported on cobalt iron with two atomic sites in lithium-oxygen batteries: The nitrogen-doped nanocarbon material supported on cobalt iron with two atomic sites is applied to lithium-oxygen batteries as a positive electrode catalyst.
[0017] The assembly method of the lithium-oxygen battery is as follows:
[0018] First, the prepared nitrogen-doped carbon nanomaterials were mixed with conductive carbon black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent to stir and mix to form a uniform slurry.
[0019] Subsequently, the slurry is evenly coated onto carbon paper and dried in a vacuum drying oven at 80-85℃ for 12-14 hours. After drying, it is cut into circular pieces with a diameter of 8-10 mm. Diethylene glycol dimethyl ether (1M LiTFSI / TEGDME) containing 1M lithium bis(trifluoromethanesulfonate) is used as the electrolyte, and lithium metal sheets with a diameter of 16 mm and glass fiber membranes are used as the negative electrode and separator, respectively. Using a Swagelok-type battery mold, the internal battery shell of the Li-O2 battery is assembled. The completed battery shell is sealed in a glass jar with an O2 gas filling pipe and an exhaust pipe. O2 gas is introduced into the glass jar at a flow rate of 30 mL / min and excess gas is expelled. After filling for 12-16 hours, the assembly of the Li-O2 battery is completed.
[0020] Beneficial effects
[0021] (1) This invention prepares a rhombohedral octahedral nitrogen-doped nanocarbon precursor assembled by vacuum-assisted heat treatment, and prepares a cobalt / iron bimetallic nitrogen-doped nanocarbon material with highly dispersed metal active sites by loading iron and cobalt elements. It has high ORR / OER bifunctional catalytic activity and can be used as a positive electrode catalytic material for organic lithium oxygen batteries.
[0022] (2) The present invention provides a novel process for preparing zeolite imidazole-based metal-organic framework ZIF-7 by vacuum-assisted heat treatment, which yields a special isomer that differs from the conventional cubic crystal form. It has a unique rhombohedral octahedral structure with self-assembled nanorod units. The nanorod units are composed of loosely packed nanospheres, which endows the material with extremely high active surface area and unique micro-nano structure.
[0023] (3) In the atomic-level bimetallic cobalt-iron supported nanorod assembly rhombohedral nitrogen-doped nanocarbon material derived from ZIF-7 described in this invention, the different ratios of iron and cobalt doping have an important impact on the catalytic activity of ORR / OER. When used in the positive electrode catalyst of lithium-oxygen batteries, it exhibits minimal charge-discharge polarization.
[0024] (4) The ZIF-7-derived atomically-sized bimetallic cobalt-iron supported nanorods assembled into rhombohedral octahedral nitrogen-doped carbon nanomaterials described in this invention can be used as positive electrode catalysts for lithium-oxygen batteries. The preparation method is simple and the conditions are mild. The bimetallic material with ORR / OER dual catalytic function exhibits high atomic-level dispersion in the carbon material, demonstrating an ultra-high discharge specific capacity (24644 mAh g) in lithium-oxygen batteries. -1) and an ultra-long cycle life (1770h). Attached Figure Description
[0025] Figure 1 Field emission scanning electron microscope (FE-SEM) image and corresponding energy dispersive spectroscopy (EDS) image of F4C1-NAS prepared for Example 1;
[0026] Figure 2 Scanning electron microscopes (SEMs) at different magnifications of the microstructure of the narrow-side end face of the F4C1-NAS rhombohedral octahedron prepared in Example 1;
[0027] Figure 3 Transmission electron microscope (TEM) image of F4C1-NAS prepared in Example 1;
[0028] Figure 4 The image shows a high-resolution transmission electron microscope (HR-TEM) image of the F4C1-NAS prepared in Example 1.
[0029] Figure 5 The high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image and the corresponding energy dispersive spectroscopy (EDS) image of F4C1-NAS prepared for Example 1;
[0030] Figure 6 The X-ray diffraction (XRD) pattern of F4C1-NAS prepared in Example 1;
[0031] Figure 7 The nitrogen adsorption-desorption isotherm and pore size distribution of F4C1-NAS prepared in Example 1;
[0032] Figure 8 The full X-ray photoelectron spectroscopy (XPS) spectrum of F4C1-NAS prepared in Example 1;
[0033] Figure 9 The high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of F4C1-NAS prepared in Example 1;
[0034] Figure 10 Cyclic voltammetry (CV) curves of the Li-O2 battery dual-electrode system with F4C1-NAS as catalyst prepared in Example 1 within a voltage window of 2.0-4.5V;
[0035] Figure 11 The initial constant current discharge / charge curve of the Li-O2 battery prepared in Example 1 using F4C1-NAS as a catalyst;
[0036] Figure 12 Discharge / charge voltage curves of the Li-O2 battery prepared in Example 1 using F4C1-NAS as a catalyst at different cycle periods;
[0037] Figure 13 The charge-discharge cycle curves and time-terminal voltage curves of the Li-O2 battery prepared in Example 1 using F4C1-NAS as a catalyst are shown.
[0038] Figure 14 Field emission scanning electron microscope (FE-SEM) image and corresponding energy dispersive spectroscopy (EDS) image of F1C1-NAS prepared for Example 2;
[0039] Figure 15 Transmission electron microscope (TEM) image of F1C1-NAS prepared in Example 2;
[0040] Figure 16 This is a high-resolution transmission electron microscope (HR-TEM) image of the F1C1-NAS prepared in Example 2;
[0041] Figure 17 The X-ray diffraction (XRD) pattern of F1C1-NAS prepared in Example 2;
[0042] Figure 18 The nitrogen adsorption-desorption isotherm and pore size distribution of F1C1-NAS prepared in Example 2 are shown below.
[0043] Figure 19 Cyclic voltammetry (CV) curves of the Li-O2 battery dual-electrode system prepared in Example 2 using F1C1-NAS as a catalyst in a voltage window of 2.0-4.5V;
[0044] Figure 20 The initial constant current discharge / charge curve of the Li-O2 battery prepared in Example 2 with F1C1-NAS as the catalyst;
[0045] Figure 21 The discharge / charge voltage curves of the Li-O2 battery prepared in Example 2 with F1C1-NAS as the catalyst under different cycle periods;
[0046] Figure 22 The image shows a high-resolution transmission electron microscope (HR-TEM) image of the F1C4-NAS prepared in Example 3.
[0047] Figure 23 The nitrogen adsorption-desorption isotherm and pore size distribution of F1C4-NAS prepared in Example 3;
[0048] Figure 24 Cyclic voltammetry (CV) curves of the Li-O2 battery dual-electrode system prepared in Example 3 using F1C4-NAS as a catalyst in a voltage window of 2.0-4.5V;
[0049] Figure 25The discharge / charge voltage curves of the Li-O2 battery prepared in Example 3 using F1C4-NAS as a catalyst at different cycle periods are shown.
[0050] Figure 26 The discharge / charge voltage curves of the Li-O2 battery prepared in Example 3 using F1C1-NAS as a catalyst at different cycle periods. Detailed Implementation
[0051] The present invention will be further described below with reference to specific embodiments. Unless otherwise specified, the methods described are conventional methods, and the raw materials, unless otherwise specified, can be obtained from publicly available commercial sources.
[0052] Example 1
[0053] (1) 5 mL of deionized water containing 110 mg Zn(CH3COO)2·2H2O was rapidly poured into 20 mL of deionized water containing 470 mg benzimidazole, while stirring. The mixture was transferred to a vacuum oven and heated at 0.02 MPa and 80 °C for 36 h. A white rhombohedral octahedral powder assembled from isomers of the zeolite imidazole-based metal-organic framework ZIF-7 was obtained.
[0054] (2) 6 mL of tetrahydrofuran (THF) solution containing 24 mg iron phthalocyanine (FePc) and 6 mg cobalt phthalocyanine (CoPc) was poured into 30 mL of tetrahydrofuran solution containing 300 mg of the above-mentioned nanorod-assembled rhombohedral octahedral ZIF-7 powder. After stirring for 24 h, the mixture was collected by centrifugation, washed three times with ethanol, and dried at 60 °C for 12 h to obtain a ZIF-7 composite material (F4C1-ZIF-7) with an iron to cobalt ratio of 4:1.
[0055] (3) The above-mentioned F4C1-ZIF-7 material was placed in a corundum boat and then placed in a tube furnace. Under a nitrogen protective atmosphere, the sample was heated to 950℃ at a heating rate of 5℃ / min for carbonization. After holding at this temperature for 3 minutes, it was naturally cooled to room temperature to obtain cobalt-iron co-supported nanorods assembled into rhombohedral octahedral nitrogen-doped nanocarbon nanomaterials. The nanomaterials were soaked in 1 mol / L hydrochloric acid and ultrasonically cleaned at 200W for 10 minutes. After filtration, the filter residue was dried in an oven at 60℃ for 12 hours to obtain F4C1-ZIF-7 derived atomic-level bimetallic cobalt-iron supported nanorods assembled into rhombohedral octahedral nitrogen-doped nanocarbon nanomaterials (F4C1-NAS).
[0056] Figure 1 Field emission scanning electron microscopy (FE-SEM) and corresponding energy dispersive spectroscopy (EDS) images of the prepared F4C1-NAS were obtained from... Figure 1As shown in (a), the microstructure of the prepared nitrogen-doped carbon nanomaterial is a rhombohedral octahedron composed of nanorods. The size of the rod-shaped nanocrystals is approximately 200 nm. The nanorods further self-assemble to form porous rhombohedral octahedrons with a length of approximately 6 μm and a width of approximately 4 μm. Figure 1 (bf) is Figure 1 (a) The energy-dispersive X-ray spectroscopy (EDS) image corresponding to the SEM shows the elemental distribution of C, O, N, Fe, and Co, indicating the successful preparation of Fe, Co, and N-doped carbon derived from ZIF-7. Figure 2 (ac) shows the narrow end face of the F4C1-NAS rhombohedral octahedron. It can be seen that there are nanospheres stacked inside the nanorod. Due to the stress shrinkage caused by high-temperature calcination, the outer surface of the end face of the nanorod is concave inward.
[0057] Figure 3 This is a transmission electron microscope (TEM) image of the F4C1-NAS. From... Figure 3 The morphology of the rhombohedral octahedral nanorods can be observed more clearly. The nanorods are approximately 500 nm long and 300 nm wide. Furthermore, at higher magnification, it can be seen that the interior of the nanorods consists of nanospheres ranging from 5 to 15 nm in size, with distinct gaps between the spheres. This open, slit-like, layered porous structure provides the material with sufficient active surface area, facilitating the transport and diffusion of gaseous reactants and electrolytes.
[0058] Figure 4 The high-resolution transmission electron microscope (HR-TEM) image of F4C1-NAS shows that no nanoscale Fe and Co metal particles were observed at higher magnifications, preliminarily ruling out the possibility that Fe and Co metals exist in the form of metal clusters or alloys. This indicates that Fe and Co are more likely to exist in atomic form on the carbon spheres assembled from nanorods. In the corresponding HR-TEM-EDS image, C, O, N, Fe, and Co elements can be seen to be uniformly dispersed inside the material.
[0059] Table 1 shows the elemental contents of Fe and Co in the F4C1-NAS sample obtained from inductively coupled plasma optical emission spectrometry (ICP-OES). The mass content of iron is 0.709%, and the mass content of cobalt is 0.191%, which translates to a molar ratio of 3.7 for iron and approximately 4 for cobalt, consistent with the designed atomic ratio. Furthermore, the elemental contents indicate the presence of relatively small Fe and Co species, suggesting that Fe and Co may exist in diatomic forms within the carbon matrix.
[0060] Figure 5This is a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image of the F4C1-NAS sample. The results show that the sample contains singly dispersed iron and cobalt atoms, and no obvious lattice fringes representing metal nanoparticles. According to the atomic number contrast rule in transmission electron microscopy, the image intensity is proportional to the square of the atomic number (Z). 2 In an image, the brighter a portion is, the higher its atomic number. However, Fe and Co have similar atomic numbers, making them difficult to distinguish in the image. Observing the corresponding EDS image confirms that Fe and Co elements are uniformly distributed in the sample.
[0061] Figure 6 The X-ray diffraction (XRD) pattern of F4C1-NAS shows peaks at 2θ of 24.5° and 43.8°, corresponding to the (002) and (101) crystal planes of carbon, respectively, confirming that the sample is amorphous carbon. Furthermore, since no other crystalline phases (such as metals, metal oxides, and metal carbides) were detected, combined with the high-resolution transmission electron microscopy (HR-TEM) image and inductively coupled plasma optical emission spectroscopy (ICP-OES) results, it can be inferred that small-sized Fe and Co species are uniformly dispersed in the carbon matrix.
[0062] Figure 7 The nitrogen adsorption-desorption isotherm of F4C1-NAS was obtained using the Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) models to determine the specific surface area, pore volume, and pore size distribution of the material. F4C1-NAS exhibits typical Type IV hysteresis loops for mesoporous carbon, with a Type IV hysteresis loop appearing when P / P0 > 0.5. According to the IUPC model, the hysteresis loop is of type H4, indicating the presence of numerous mesopores within the porous carbon. The specific surface area and average pore size of F4C1-NAS are 300.964 μm. 2 g -1 And 3.849nm.
[0063] Figure 8 The X-ray photoelectron spectroscopy (XPS) full spectrum of F4C1-NAS characterizes the chemical composition and elemental valence states of the material. The XPS full spectrum of F4C1-NAS shows clear signals of carbon, oxygen, and nitrogen, while iron and cobalt are present in low concentrations, therefore no obvious metallic signals were detected.
[0064] Figure 9 High-resolution XPS spectra of different elements in F4C1-NAS. Figure 8The C1s spectrum in (a) shows peaks for C=C, CN, COC, and C=O at 284.6 eV, 286.7 eV, 287.5 eV, and 289.3 eV, proving the presence of carbon-oxygen functional groups. Figure 8 (b) The high-resolution N1s spectrum shows peaks at 398.3, 399.5, 400.6, 402.3, and 405.2 eV, corresponding to pyridine nitrogen, metal-nitrogen, pyrrole nitrogen, graphitic nitrogen, and nitrogen oxides, respectively. In the high-resolution Fe 2p XPS spectrum ( Figure 8 In (c)), Fe2p can be fitted. 3 / 2 The peaks at 733.5, 728.3, 725.7, and 723.9 eV of the orbital correspond to Fe, respectively. 3+ (satellite peak), Fe 2+ (satellite peak), Fe 3+ and Fe 2+ The peaks at 718.8, 714.7, 712.8, and 711.0 belong to the Fe 2p orbital, respectively. 1 / 2 Fe 3+ (satellite peak), Fe 2+ (satellite peak), Fe 3+ and Fe 2+ Orbital. In high-resolution Co 2p XPS spectra ( Figure 8 In (d), peaks at 778.6, 782.2, and 786.11 eV can be fitted, corresponding to Co 2p, respectively. 3 / 2 Co of the orbit 3+ Co 2+ The satellite peaks, located at 791.2, 795.1, and 802 eV, correspond to Co 2p, respectively. 1 / 2 Co of the orbit 3+ Co 2+ The satellite peaks indicate that the cobalt / iron and nitrogen elements in the diatomic catalyst are Co / Fe-N. x The coordination mode.
[0065] The above characterization confirms that the F4C1-ZIF-7 derived atomically bimetallic cobalt-iron supported nanorod assembly rhombohedral octahedral nitrogen-doped carbon nanomaterial (F4C1-NAS) prepared in this embodiment is a diatomic cobalt-iron supported material, and is Fe / Co-N. x Coordination.
[0066] The prepared nanorods were assembled into rhombohedral octahedral nitrogen-doped carbon nanomaterials to form the positive electrode of a lithium-oxygen (Li-O2) battery: First, the prepared nitrogen-doped carbon nanomaterials were mixed with conductive carbon black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent to stir and mix to form a uniform slurry; then, the slurry was uniformly coated onto carbon paper and dried in a vacuum drying oven at 80°C for 12 hours. After drying, it was cut into discs with a diameter of 10 mm; using diethylene glycol dimethyl ether (1M LiTFSI / TEGDME) containing 1M lithium bis(trifluoromethanesulfonate) as the electrolyte, a 16 mm diameter lithium metal sheet and a glass fiber membrane as the negative electrode and separator, respectively, the battery shell inside the Li-O2 battery was assembled using a Swagelok-type battery mold. The completed battery casing was sealed in a glass jar equipped with an O2 gas filling tube and an venting tube. O2 gas was introduced into the glass jar at a flow rate of 30 mL / min, and excess gas was expelled. After 12 hours of filling, the assembly of the Li-O2 battery was completed.
[0067] The battery tester (LAND-CT2001A) is used for constant current discharge / charge testing and cycle performance testing, with a current density range of 0.02–0.2 mA cm⁻¹. -2 The discharge / charge voltage plateau was limited to 2.0–4.5 V. Cyclic voltammetry (CV) measurements were performed on a CHI660 electrochemical workstation using a dual-electrode system. A lithium metal sheet served as both the counter and reference electrode, while a carbon catalyst electrode was used as the working electrode. The active area of the positive electrode material was 0.5 cm². 2 The scan rate is 1 mV / s -1 The voltage window is 2.0-5.0V (vs. Li). + / Li).
[0068] Figure 10 The assembled Li-O2 battery was scanned at a rate of 0.2 mV / s. -1 Cyclic voltammetry (CV) curves of the lithium-oxygen battery dual-electrode system within a voltage window of 2.0–4.5 V are shown. A pair of significant redox peaks are observed; the reduction peak corresponds to the onset potential of the ORR process, approximately 2.8 V. The first anodic oxidation peak appears around 3.0 V, and a second anodic peak appears at 4.0 V as the oxidation process continues. The relatively low OER onset potential indicates that Fe / Co plays a significant role in the catalytic activity of the reaction.
[0069] Figure 11 With a current density of 0.02 mA / cm² -2 The initial constant current discharge / charge curve of the battery is shown when the voltage window is 2.0-4.5V. The discharge and charge voltage plateaus can be seen to be... Figure 9The onset potential of the CV curve closely corresponds to that of the battery. With a positive electrode active material mass of 0.3 mg, the battery's discharge specific capacity can reach 24644 mAh g. -1 And in 17232mAh g -1 Previously, it had been below 4.0V, maintaining a low charging voltage platform.
[0070] Cyclic stability is a key indicator for evaluating the performance of Li-O2 batteries. Figure 12 The result shows that at a current density of 0.02 mA / cm² -2 The discharge / charge voltage curves of the battery at different cycle periods. (At 1000mAh g) -1 At the cutoff capacity, the battery exhibits an exceptionally long cycle life, capable of cycling continuously for 1000 hours without capacity decay. Furthermore, the battery demonstrates extremely low voltage hysteresis, with an initial hysteresis of approximately 0.5V. As cycling progresses, the voltage hysteresis gradually increases to 0.8V, ultimately remaining below 1.5V. The time-voltage curves show that the battery can stably cycle for 1770 hours with minimal polarization, demonstrating an exceptionally long cycle life and high energy conversion efficiency.
[0071] Figure 13 (a) is a high current density of 0.2 mA cm⁻¹ -2 and 500mA hg -1 Cycling curves at cutoff capacity. It can be seen that the battery cycles for over 700 cycles under stable charge / discharge voltage. The time-mid-voltage curve (Figure b) shows extremely small charge and discharge polarization. After 600 hours of cycling, the voltage hysteresis stabilizes within the range of 0.5V, which is one of the lowest voltage hysteresis values currently available, and its performance is close to that of Pt and Au nanocatalysts. At high current densities, the nitrogen-doped carbon nanotubes derived from F4C1-ZIF-7 possess both ORR / OER catalytic functions and can serve as a bifunctional catalyst for the positive electrode of Li-O2 batteries, reducing parasitic and side reactions. Further discharge cutoff capacity of 1000 mA hg is achieved. -1 Under normal conditions, when the F4C1-NAS is in stable cycling for 60 cycles, the charging voltage plateau is still below 4.0V.
[0072] The test results of the Li-O2 battery above show that the prepared F4C1-ZIF-7 derived atomically-level bimetallic cobalt-iron supported nanorod-assembled rhombohedral octahedral nitrogen-doped carbon nanomaterials, due to their higher proportion of Fe single-atom active sites, can efficiently catalyze the ORR process, promote the generation of tiny Li2O2 products, and form a uniform F4C1-NAS / Li2O2 hybrid structure. Conversely, this uniform hybrid structure also facilitates the decomposition of Li2O2, i.e., the OER process, thereby reducing the overpotential during charging.
[0073] In summary, the battery exhibits excellent cycle stability and high energy conversion efficiency. This is due to (1) a reasonable porous structure and channels in the positive electrode, namely, the hierarchical structure composed of nanorod units formed by the stacking of loose nanospheres and rhombohedral octahedrons formed by the self-assembly of nanorod units, which ensures that the battery will not collapse and become blocked after multiple charging and discharging cycles, thus giving the battery excellent cycle stability. (2) It has excellent conductivity and high mass transfer rate, which can efficiently decompose discharge products during charging and extend the battery cycle life. At the same time, the reduction in the charging voltage can also improve the energy conversion efficiency of the battery. (3) Carbon materials supported / doped with transition metals Fe and Co elements still exhibit good catalytic activity at high rates, maintaining a low charge and discharge overpotential, which can prevent the positive electrode carbon from decomposing at high voltage, thereby improving the cycle stability of the battery. Fe and Co catalysts with high single-atom Fe content, as positive electrode catalysts for Li-O2 batteries, can provide more active sites such as defects and electron-withdrawing centers, which not only play an important role in electrocatalytic activity but also make the catalyst more stable.
[0074] Example 2
[0075] Based on Example 1, except that the mass of iron phthalocyanine and cobalt phthalocyanine was changed from 24 mg and 6 mg to 15 mg and 15 mg respectively, i.e. the molar ratio of iron to cobalt atoms was 1:1, all other steps and conditions were the same as in Example 1. Accordingly, an atomically-level bimetallic cobalt-iron supported nanorod assembly rhombohedral octahedral nitrogen-doped nanocarbon nanomaterial (F1C1-NAS) was obtained.
[0076] Figure 14 Field emission scanning electron microscopy (FE-SEM) and energy dispersive spectroscopy (EDS) images of the prepared F1C1-NAS, from... Figure 1 As can be seen in (a), the prepared F1C4-NAS has a similar microstructure to that of Example 1. Figure 1 (bf) is Figure 1 (a) Energy dispersive spectroscopy (EDS) image corresponding to SEM, illustrating the successful preparation of Fe, Co and N-doped carbon derived from ZIF-7. Figure 15 The image shows a transmission electron microscope (TEM) image of F1C1-NAS, which reveals a structural morphology similar to that of Example 1.
[0077] Figure 16The high-resolution transmission electron microscope (HR-TEM) image of F1C1-NAS shows that no nanoscale Fe and Co metal particles were observed at higher magnifications, preliminarily ruling out the possibility that Fe and Co metals exist in the form of metal clusters or alloys. This indicates that Fe and Co are more likely to exist in atomic form on the carbon spheres assembled from nanorods. In the corresponding HR-TEM-EDS image, C, O, N, Fe, and Co elements can be seen to be uniformly dispersed inside the material.
[0078] Table 1 shows the elemental contents of Fe and Co in the F1C1-NAS sample obtained from inductively coupled plasma optical emission spectrometry (ICP-OES). The mass content of iron is 0.384%, and the mass content of cobalt is 0.389%, which translates to a molar ratio of approximately 1 for iron and cobalt, consistent with the designed atomic ratio. Furthermore, the elemental contents indicate the presence of relatively small Fe and Co species, suggesting that Fe and Co may exist in diatomic forms within the carbon matrix.
[0079] Figure 17 The X-ray diffraction (XRD) pattern of F1C1-NAS confirms that the sample is amorphous carbon and no other crystalline phases (metals, metal oxides and metal carbides) were detected. Combined with the high-resolution transmission electron microscopy (HR-TEM) pattern and the results of inductively coupled plasma optical emission spectroscopy (ICP-OES), it is further confirmed that small-sized Fe and Co species are uniformly dispersed in the carbon matrix.
[0080] Figure 18 The nitrogen adsorption-desorption isotherm for F1C1-NAS is shown, along with the corresponding specific surface area, pore volume, and pore size distribution. The specific surface area and average pore size of F1C1-NAS are 251.891 m² / s. 2 g -1 And 3.844nm.
[0081] To investigate the catalytic activity of the prepared F1C1-ZIF-7-derived atomically-scale bimetallic cobalt-iron supported nanorod-assembled rhombohedral nitrogen-doped carbon nanomaterial (F1C1-NAS) as an oxygen electrode catalyst for Li-O2 batteries, it was prepared as a positive electrode for Li-O2 batteries, and its electrochemical performance was investigated. The preparation process was the same as in Example 1.
[0082] Figure 19 The assembled Li-O2 battery was scanned at a rate of 0.2 mV / s. -1 Cyclic voltammetry (CV) curves of the lithium-oxygen battery dual-electrode system within a voltage window of 2.0–4.5 V are shown. A pair of relatively distinct redox peaks can be observed; the reduction peak corresponds to the onset potential of the ORR process, approximately 2.6 V.
[0083] Figure 20 With a current density of 0.02 mA / cm² -2 The initial constant current discharge / charge curve of the battery is shown when the voltage window is 2.0-4.5V. It can be seen that the battery's discharge specific capacity can reach 20388mAh g. -1 . Figure 21 For the battery at a current density of 0.02 mA cm⁻¹ -2 Discharge depth of 1000mAh g -1 The discharge / charge voltage curves of the battery at different cycle periods are shown. It can be seen that after 60 cycles, the discharge plateau of the battery stabilizes above 2.5V, while the charging voltage remains below 4.2V. This indicates that when the atomic ratio of iron to cobalt is 1:1, the rhombohedral octahedral nitrogen-doped carbon nanomaterials assembled from nanorods (F1C1-NAS) also exhibit considerable discharge specific capacity and low charging overpotential, demonstrating excellent catalytic activity, and the prepared Li-O2 battery can also cycle stably.
[0084] Example 3
[0085] Based on Example 1, except that the mass of iron phthalocyanine and cobalt phthalocyanine was changed from 24 mg and 6 mg to 6 mg and 24 mg respectively, i.e. the molar ratio of iron to cobalt atoms was 1:4, all other steps and conditions were the same as in Example 1. Accordingly, an atomic-level bimetallic cobalt-iron supported nanorod assembly rhombohedral octahedral nitrogen-doped nanocarbon nanomaterial (F1C4-NAS) was obtained.
[0086] Figure 22 The high-resolution transmission electron microscope (HR-TEM) image of F1C4-NAS also shows no nanoscale Fe and Co metal particles, ruling out the possibility that Fe and Co metals exist in the form of metal clusters or alloys. This suggests that Fe and Co are more likely to exist in the form of atoms on the carbon spheres assembled from nanorods and be uniformly distributed.
[0087] Table 1 shows the elemental contents of Fe and Co in the F1C4-NAS sample obtained from inductively coupled plasma optical emission spectrometry (ICP-OES). The mass content of iron is 0.012%, and the mass content of cobalt is 0.032%, which translates to an approximate molar ratio of 0.375 for iron and cobalt. The elemental contents are consistent with the range where smaller Fe and Co species are present, suggesting that Fe and Co may exist in diatomic forms within the carbon matrix.
[0088] Figure 23 The nitrogen adsorption-desorption isotherms for F1C4-NAS are shown, along with the corresponding specific surface area, pore volume, and pore size distribution. The specific surface area and average pore size of F1C1-NAS are 204.852 m² / s. 2 g-1 And 3.845nm.
[0089] To investigate the catalytic activity of the prepared F1C4-ZIF-7-derived atomically-scale bimetallic cobalt-iron supported nanorod-assembled rhombohedral octahedral nitrogen-doped carbon nanomaterial (F1C4-NAS) as an oxygen electrode catalyst in a Li-O2 battery, it was prepared as a positive electrode in a Li-O2 battery, and its electrochemical performance was investigated. The preparation process was the same as in Example 1.
[0090] Figure 24 The assembled Li-O2 battery was scanned at a rate of 0.2 mV / s. -1 The cyclic voltammetry (CV) curves of the lithium-oxygen battery dual-electrode system within a voltage window of 2.0–4.5 V are shown. A pair of relatively obvious redox peaks can be observed.
[0091] Figure 25 With a current density of 0.02 mA / cm² -2 The initial constant current discharge / charge curve of the battery is shown when the voltage window is 2.0-4.5V. It can be seen that the battery's discharge specific capacity can reach 18482 mAh g. -1 . Figure 26 For the battery at a current density of 0.02 mA cm⁻¹ -2 Discharge depth of 1000mAh g -1 The discharge / charge voltage curves of the battery at different cycle periods are shown. It can be seen that after 60 cycles, the discharge plateau of the battery stabilizes above 2.5V, while the charging voltage remains below 4.4V. This indicates that when the atomic ratio of iron to cobalt is 1:4, the rhombohedral octahedral nitrogen-doped carbon nanomaterials assembled from nanorods (F1C4-NAS) also exhibit considerable discharge specific capacity and excellent catalytic activity, and the prepared Li-O2 battery also demonstrates stable cycle performance.
[0092] Table 1 shows the inductively coupled plasma emission spectra (ICP-OES) of F4C1-NAS, F1C1-NAS, and F1C4-NAS.
[0093]
[0094]
[0095] In summary, the above are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing nitrogen-doped carbon nanomaterials supported on cobalt-iron with two metallic atomic sites, characterized in that... The steps of this method include: The first step involves mixing an aqueous solution of zinc acetate dihydrate and an aqueous solution of benzimidazole to obtain a mixture. This mixture is then subjected to vacuum isothermal heating to obtain a white powdered zeolite imidazole-based metal-organic framework. This white powdered zeolite imidazole-based metal-organic framework is then added to a tetrahydrofuran solvent to obtain a ZIF-7 solution. The pressure during vacuum isothermal heating is 0.02-0.10 MPa, the temperature is 78-82 ℃, and the heating time is 24-36 h. The second step involves mixing cobalt and iron sources in tetrahydrofuran solvent to obtain a suspension. The suspension is then poured into the ZIF-7 solution obtained in the first step and stirred for 22-26 hours. After stirring, the mixture is centrifuged. The centrifuged product is washed with ethanol and dried to obtain a zeolite imidazole-based metal-organic framework ZIF-7 composite material containing iron and cobalt ions. The third step involves carbonizing the ZIF-7 composite material obtained in the second step at 950-1000℃ for 2-3 hours under a nitrogen or inert gas protective atmosphere to obtain nitrogen-doped nanocarbon materials supported by cobalt and iron. After etching with hydrochloric acid, the resulting product is a rhombohedral octahedral nitrogen-doped nanocarbon material derived from ZIF-7 and supported by atomically bimetallic cobalt and iron nanorods.
2. The method for preparing nitrogen-doped carbon nanomaterials supported on cobalt-iron with two metallic atomic sites according to claim 1, characterized in that: In the first step, the concentration of the aqueous solution of zinc acetate dihydrate is 20-24 mg / mL, the concentration of the aqueous solution of benzimidazole is 20-24 mg / mL, and the mass ratio of the solute in the aqueous solution of zinc acetate dihydrate to the solute in the aqueous solution of benzimidazole is 0.2-0.3:1; when the aqueous solution of zinc acetate dihydrate and the aqueous solution of benzimidazole are mixed, it means that the aqueous solution of zinc acetate dihydrate is poured into the aqueous solution of benzimidazole which is being stirred.
3. The method for preparing nitrogen-doped carbon nanomaterials supported on cobalt-iron metal diatomic sites according to claim 1, characterized in that: In the first step, the concentration of the ZIF-7 solution is 8-12 mg / mL.
4. The method for preparing nitrogen-doped carbon nanomaterials supported on cobalt-iron with two metallic atomic sites according to claim 1, characterized in that: In the third step, the hydrochloric acid concentration is 0.5-1 mol / L, and the acid etching process is performed by ultrasonication at an ultrasonic power of 200-220 W for 10-30 min.
5. A nitrogen-doped carbon nanomaterial supported on cobalt-iron with two metallic atomic sites, prepared by the method according to any one of claims 1-4, characterized in that: The nitrogen-doped carbon nanomaterial includes a nitrogen-doped carbon substrate with a porous structure and atomically distributed iron and cobalt sites loaded on the nitrogen-doped carbon substrate.
6. An application of the nitrogen-doped carbon nanomaterial supported on cobalt-iron with two metallic atomic sites as described in claim 5, characterized in that: Nitrogen-doped carbon nanomaterials supported on cobalt-iron metal with two atomic sites are used as positive electrode catalysts in lithium-oxygen batteries.
7. The application according to claim 6, characterized in that: The assembly method of the lithium-oxygen battery is as follows: First, the prepared nitrogen-doped carbon nanomaterials, conductive carbon black, and polyvinylidene fluoride binder are mixed in a mass ratio of 8:1:1, with N-methylpyrrolidone as the solvent, and stirred to form a uniform slurry. Subsequently, the slurry was evenly coated onto carbon paper and dried in a vacuum drying oven at 80-85℃ for 12-14 hours. After drying, it was cut into circular pieces with a diameter of 8-10 mm. Diethylene glycol dimethyl ether containing 1 M lithium bis(trifluoromethanesulfonate)imide was used as the electrolyte, and lithium metal sheets with a diameter of 16 mm and glass fiber membranes were used as the negative electrode and separator, respectively. Using Swagelok-type battery molds, the internal battery casing of the Li-O2 battery was assembled. The completed battery casing was sealed in a glass jar with an O2 gas filling pipe and an exhaust pipe. O2 gas was introduced into the glass jar at a flow rate of 30 mL / min and excess gas was expelled. After filling for 12-16 hours, the assembly of the Li-O2 battery was completed.
Citation Information
Patent Citations
Fe-N-C catalyst as well as preparation and application thereof
CN111313040A
Iron-cobalt diatomic catalyst applied to oxygen reduction reaction as well as preparation method and application of iron-cobalt diatomic catalyst
CN116826085A